Design and Development of the High Voltage Capacitor Step-down Power-taking Device. (May 2020) - Shuai, Zhang; Cong, Ma; Peng, Wu; Lin, Xing
Abstract: The designed device uses high voltage capacitor in series with a voltage transformer to take power. It uses the capacitance voltage resistance and the transforming characteristics of voltage transformer, and the monitoring system is supplied with power by subsequent rectifier filtering and switching circuit. As high voltage capacitor step-down has the problem of limited energy, the set of device uses voltage transformer to increase power output, and the required power are provided to the load end on the basis of the changing of the load end power, and through the relay's on or off to control the connection or disconnection of the front-end resistance. 10kv voltage transformer are used for 110kv line, and the primary side voltage of the voltage transformer is controlled at 10kV by using the voltage stabilizing function of the rear-connected circuit. Through The overall test of power output is stable, the device operates well.can provide stable and effective low-voltage power supply for the on-line detection device of 110kV high-voltage multiple circuit..